PLANEJAMENTO, ELABORAÇÃO E UTILIZAÇÃO DE MATERIAIS DIDÁTICOS DISPONIBILIZADOS EM AMBIENTE VIRTUAL DE APRENDIZAGEM - FAIM, REGIANE MARIA TOMÉ (2018)
This study is aimed at the teaching practices in the distance education modality and seeks to answer the research problem "what perceptions do the students of the Distance Education Pedagogy course have on the planning, elaboration and use of didactic material made available in the Virtual Learning Environment?" The research reflects upon the experiences of students through their narratives, regarding the VLE, considering the use of resources and activities available in it, as well as the contributions of the VLE to the teaching-learning process and teacher training. A qualitative investigative research has been developed, using the narrative inquiry presented by Clandinin and Connelly (2015) and relying on studies about the biographical research such as Delory-Momberger (2012); Passeggi (2011); Azevedo (2015). The analysis of the narratives is based on the hermeneutic-phenomenological approach, by van Manen (1990) in which Maximina Freire (2010, 2012, 2015) based her research to describe and interpret the essence of the experience lived by the participants of this investigation.The theoretical framework of this study is also composed by Kearsley and Moore (2007); Behar (2009); Moran (2009); Palloff and Pratt (2002); Paulo Freire (1996); Tardif (2014); Nóvoa (2009), Azevedo (2014); Bahia (2015); Ricardo (2013); Silva (2013); Mizukami (1986); Filatro and Cairo (2015); Clementino (2015); among others. At first, this research approaches aspects of the Distance Education, Teaching in the 21st Century and the teaching authorship. It then deals with theories and conceptions of the virtual learning environment, pedagogical planning for distance education and the production of didactic material. Afterwards, based on the hermeneutic-phenomenological analysis, in addition to the interpretation of the textual records of the experiences lived by participants in the VLE, the essence of the phenomenon is reached through the processes of textualization and thematization (operationalized by the routines of organization and interpretation). From the cycle of validation, the four major themes emerged: search, fluency, paths and mediation, which enabled, by its unfolding, reflections on distance learning, content planning, use of resources and activities in VLE and interaction between teachers and students, which can and should continue to be the main objective of professionals who work or may come to work in the distance education.